Current State of Antimicrobial Stewardship at Solid Organ and Hematopoietic Cell Transplant Centers in the United States. (26th July 2016) - Seo, Susan K.; Lo, Kaming; Abbo, Lilian M.
Abstract : OBJECTIVE: To assess the extent of antimicrobial stewardship programs (ASPs) at solid organ transplant (SOT) and hematopoietic cell transplant (HCT) centers in the United States. DESIGN: An 18-item voluntary survey was developed to gauge current antimicrobial stewardship practices in transplant patients, examine the availability and perceived usefulness of novel diagnostics and azole levels to guide therapy, and identify challenges for implementation of ASPs at these centers. PARTICIPANTS: The survey was distributed electronically to infectious disease physicians and pharmacists at adult and pediatric SOT and HCT centers during May 1–22, 2015. Facilities were deidentified. RESULTS: After duplicate removal, 71 (56%) of 127 unique transplant centers in 32 states were analyzed. Forty-four sites (62%) performed at least 100 SOT annually, and 40 (56%) performed at least 100 HCT annually. Top 5 stewardship activities encompassing transplant patients were formulary restriction, guideline development, prospective audit and feedback, education, and dose optimization. Respiratory viral panels (66/66 [100%]), azole levels (64/66 [97%]), and serum/bronchoalveolar lavage galactomannan (58/66 [88%]) were perceived as most useful to guide therapy. Apparent challenges to antimicrobial stewardship included undefined duration for certain infections (53/59 [90%]), diagnostic uncertainty (47/59 [80%]), the perception that antibiotic-resistant infections required escalation (42/59 [71%]), prescriber opposition (41/59 [69%]), and costly drugs (37/59 [63%]). CONCLUSIONS: ASP activities were performed at many adult and pediatric SOT and HCT centers in the United States. Diagnostic and therapeutic uncertainty in transplant patients is challenging for ASPs. Collaborative research should examine the impact of antimicrobial stewardship practices in SOT and HCT. Infect Control Hosp Epidemiol 2016;1–6